2010
DOI: 10.1002/cyto.a.20879
|View full text |Cite
|
Sign up to set email alerts
|

Febrile temperature but not proinflammatory cytokines promotes phosphatidylserine expression on Plasmodium falciparum malaria‐infected red blood cells during parasite maturation

Abstract: Intraerythrocytic maturation of the malaria parasite Plasmodium falciparum is associated with profound changes in the asymmetry of phospholipids in the lipid bilayer of the parasitized red blood cells (pRBCs). These changes may contribute to adherence of pRBCs to endothelial cells. This study investigates the effect of febrile temperature and proinflammatory cytokines on phosphatidylserine (PS) expression on the exofacial surface of pRBCs during parasite maturation. The expression of PS on the pRBCs was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…This behavior may be responsible for an overestimation of the b i values for the iRBC probes, which is also suggested by the average rupture forces determined strictly from single rupture event curves in the ranges presented in Table 2, i.e, 37 ± 1.9 pN (37°C) and 30 ± 1.6 pN (37°C/40°C(1h)) with p = 0.005, which compare, respectively, with b 1 = 43 pN at 37°C and b 1 = 34 pN at 37°C/40°C(1h) in Figures 4(b) and 5(c). Nonetheless, non-specific binding is expected to increase with febrile temperature exposure [40] and cannot justify the observed decrease in the single-molecule binding force (Δ b 1 in Table 1). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior may be responsible for an overestimation of the b i values for the iRBC probes, which is also suggested by the average rupture forces determined strictly from single rupture event curves in the ranges presented in Table 2, i.e, 37 ± 1.9 pN (37°C) and 30 ± 1.6 pN (37°C/40°C(1h)) with p = 0.005, which compare, respectively, with b 1 = 43 pN at 37°C and b 1 = 34 pN at 37°C/40°C(1h) in Figures 4(b) and 5(c). Nonetheless, non-specific binding is expected to increase with febrile temperature exposure [40] and cannot justify the observed decrease in the single-molecule binding force (Δ b 1 in Table 1). …”
Section: Discussionmentioning
confidence: 99%
“…In this study, heating ring-stage iRBCs to 40 °C for 2 h enhanced the number of adherent cells and was associated with an increase in trafficking of Pf EMP1 to the cell surface.However, this effect seems absent in mature stages since the mean level of Pf EMP1 expression has not been altered by the transient exposure to 40 °C (Figure 6). On the other hand, febrile temperatures are known to promote phosphatidylserine expression on iRBCs membranes during parasite maturation [40]. This additional display of non–specific receptors may justify the increase in binding frequency observed for iRBC after exposure to febrile temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was already reported that in P. falciparum in vitro cultures nRBCs are marked by PS externalization (Koka et al, 2007; Pattanapanyasat et al, 2010), and in our previous study with BALB/c mice infected by the lethal P. yoelii 17XL parasites, increased levels of nRBC apoptosis correlated with hiperparasitemia (Totino et al, 2013), indirectly suggesting that as do bacterial toxins (listeriolysin from Listeria monocytogenes and hemolysin from Vibrio parahaemolyticus ), peptidoglycan, and Schistosoma mansoni egg antigens (Lang et al, 2004b; Föller et al, 2007; Kasinathan and Greenberg, 2010; Jilani et al, 2012; Abed et al, 2013), plasmodial antigens can play a role in induction of erythrocytic apoptosis.…”
Section: Malaria and Erythrocytic Apoptosis Inducersmentioning
confidence: 99%
“…In vitro studies have shown that P. falciparum growth rates and development were accelerated when parasites were exposed to 40 °C for 2 h, incubated at 37 °C for 10 h and again exposed to 40 °C for 12–24 h. 9 The parasite life cycle was also accelerated after exposure to less severe temperatures of 38.5–39 °C. 10 Incubation at 40 °C for 1–2 h enhanced the cytoadherence of mature P. falciparum -infected erythrocytes (pRBC) to CD36 and ICAM-1 receptors and also caused adherence of ring-stage parasites, which do not normally bind to these receptors. 11 Febrile temperatures have also been shown to reduce the deformability of pRBC, which may aid in sequestration, 12 as well inducing phosphatidylserine (PS) externalisation in pRBC.…”
mentioning
confidence: 99%
“…11 Febrile temperatures have also been shown to reduce the deformability of pRBC, which may aid in sequestration, 12 as well inducing phosphatidylserine (PS) externalisation in pRBC. 10 …”
mentioning
confidence: 99%